Prophylactic effect of hot pack on symptoms of eccentric exercise-induced muscle damage of the wrist extensors - Khamwong P. (2017)
This study investigated whether hot pack treatment could provide prophylactic effects on muscle damage induced by eccentric exercise of the wrist extensors. Twenty-eight healthy men (age 21±1 years, weight 65±16 kg, height 171±6 cm) were randomly placed into hot pack (n = 14) and control (n = 14) groups. All participants performed an exercise consisting of 300 maximal eccentric contractions of the wrist extensors of the non-dominant arm using an isokinetic dynamometer. A hot pack was applied for 20 min to the wrist extensors of the exercised arm before the exercise for the hot pack group. The control group received no treatment before the exercise. Measured variables included pain intensity assessed by a visual analogue scale and a modified Likert's scale, cold thermal pain threshold, pressure pain threshold (PPT), range of motion in active wrist flexion (ROM-AF) and extension (ROM-AE), range of motion in passive wrist flexion (ROM-PF) and extension (ROM-PE), grip strength, and wrist extension strength. Changes in these variables before, immediately after, and 1 to 8 days following the exercise were compared between groups by a two-way repeated measures ANOVA. All outcome measures from both groups (except for the cold thermal pain threshold of the hot pack group) demonstrated a significant change within the first 2-3 days following exercise. Significant differences between groups were only found at a single point in time for PPT, ROM-PF, ROM-PE and ROM-AE, and the changes were smaller for the hot pack group in comparison to the control group. These results suggest that the prophylactic effects of hot pack treatment on eccentric exercise-induced muscle damage of the wrist extensors are limited. © 2012 Copyright European College of Sport Science.